Assessing Acceptability of Short Message Service Based Interventions towards Becoming Future Voluntary Blood Donors. (10th November 2014) - Saleem, Sana; Wasim, Anum; Sabih, Sidra; Khan, Ayisha Farooq; Rizvi, Madiha Hasan; Jillani, Umaima Ayesha; Syed, Mujtaba Jamal; Mumtaz, Madiha; Mumtaz, Yasmeen; Shehzad, Abdul Moid; Dawani, Om; Khan, Saima; et al.
Abstract : All blood bank services, especially those of developing countries, face a major shortfall of blood donations due to lack of voluntary blood donors. Our study aims to evaluate the acceptability of Short Message Service based interventions towards becoming voluntary blood donors among medical university students of Karachi, Pakistan. Methods . A total of 350 medical students were approached in medical universities of Karachi, Pakistan, using a nonprobability convenient sampling technique. Data collectors administered a self-made questionnaire to each participant using an interview based format. All data was recorded and analyzed on SPSS 16. Results . 350 participants, having a mean age of 21.47 ± 1.36, were included in our study with 30.6% (107/350) being males and 69.4% (243/350) being females. 93.4% (327/350) of participants agreed that donating blood was healthy, but only 26% had donated blood in the past with 79.1% donating voluntarily. 65.7% (230/350) of the participants agreed to take part in Short Message Service based behavioral interventions to become voluntary blood donors with 69.7% (244/350) also agreeing that Short Message Service reminders will promote them to donate blood more often. Conclusion . With university students willing to become voluntary blood donors, Pakistani blood banks can carry out Short Message Service based interventions to encourage them to donate blood.